Intervensi Pekerja Sosial Dalam Menangani Mental Health Dengan Menggunakan Teori Psikodinamik - Yoga Pratama; Rizki Hidayat; Alfinda Meisya Larasati; Ati Kusmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Mental health is a very important aspect of an individual's well-being, and societal understanding plays a central role in shaping attitudes and responses to mental health issues. This research applies a psychodynamic approach to deepen society's understanding of mental health. This approach involves understanding psychodynamic concepts, such as unconscious conflict, self-defense, and personality structure, to explore the root causes of mental health problems in society. A psychodynamic approach is used to discuss how unequal access to resources and education can influence society's understanding of mental health. Empowerment strategies and increasing self-awareness are also recommended to overcome internal conflicts that can affect an individual's mental health.